English for Tourism : Peningkatan Kemampuan Komunikasi Bahasa Inggris Bagi Anggota Geopark Youth Forum Kabupaten Lebak - Siti Hanna Sumedi; Hikmah Pravitasari (Jurnal Dharmabakti Nagri, 2023)
Improving English language communication skills is crucial for members of the Geopark Youth Forum (GYF) in Kabupaten Lebak to face the growing tourism sector. This study aims to conduct a community engagement program entitled "English for Tourism: Enhancing English Communication Skills for Members of the Geopark Youth Forum Kabupaten Lebak" to enhance the quality of tourism services through improved English language proficiency. The community engagement program includes an "English for Tourism" workshop that covers tourism-related vocabulary, daily conversations with tourists, and presentation of tourist attraction Geopark Bayah Dome. The implementation method involves needs analysis, curriculum development, facilitator training, pre-test, and post-test evaluation to measure the participants' progress in language proficiency. The results of the community engagement program indicate a significant improvement in the English language communication skills of GYF participants in Kabupaten Lebak. Pre-test and post-test scores show an average increase of 30 points in English language proficiency, showing the workshop's success in enhancing language skills. Participant evaluations also indicate that the workshop provides tangible benefits, boosting their confidence in speaking English and enhancing their understanding of tourism-related terms. This community engagement program is expected to make a positive contribution to the development of the tourism sector in the region of Kabupaten Lebak. As English communication skills of the participants improved, GYF members can provide better services to foreign tourists, elevate tourists' experiences in the region, and support the development of tourism potential. Furthermore, the successful implementation of this program emphasizes the importance of collaboration between the university and stakeholders in supporting community development and the tourism sector in Kabupaten Lebak.